1999
DOI: 10.1042/0264-6021:3390759
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor and epidermal growth factor stimulate clusterin gene expression in PC12 cells

Abstract: Clusterin (apolipoprotein J) is an extracellular glycoprotein that might exert functions in development, cell death and lipid transport. Clusterin gene expression is elevated at sites of tissue remodelling, such as differentiation and apoptosis; however, the signals responsible for this regulation have not been identified. We use here the clusterin gene as a model system to examine expression in PC12 cells under the control of differentiation and proliferation signals produced by nerve growth factor (NGF) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
2
21
0
2
Order By: Relevance
“…Together, these data suggest that clusterin must be involved in differentiation-and proliferation-signalling pathways. Further, it was found that NGF and EGF use the common Ras-extracellular signal-regulated kinase-AP1 (activator protein 1, a transcription factor of clusterin) signalling pathway to activate clusterin gene expression [10]. We also found simultaneous activation of MAPKs and an increase of clusterin expression during islet-cell regeneration.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Together, these data suggest that clusterin must be involved in differentiation-and proliferation-signalling pathways. Further, it was found that NGF and EGF use the common Ras-extracellular signal-regulated kinase-AP1 (activator protein 1, a transcription factor of clusterin) signalling pathway to activate clusterin gene expression [10]. We also found simultaneous activation of MAPKs and an increase of clusterin expression during islet-cell regeneration.…”
Section: Discussionmentioning
confidence: 60%
“…However, the mechanism for islet cell regeneration has not been shown. Clusterin is known to be up-regulated at sites of tissue remodelling through differentiation and proliferation after apoptosis [10,14,16,41]. We have reported the expression of clusterin in the developing pancreas and in the pancreatic tissue of the streptozotocin treated rats and suggested that this protein must play important roles [7,20].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…CLU mRNA was induced and activated in PC12 prostate cancer cells by nerve growth factor and epidermal growth factor. 34 Transforming growth factor beta (TGF-b) induces CLU gene expression in a variety of cell types. Transforming growth factor beta-1 (TGF-b1) was shown to enhance sCLU protein and mRNA expression in thyroid epithelial cells, and it was proposed that upregulation of CLU expression may be a marker of TGF-b1-mediated thyrocyte dedifferentiation.…”
Section: Regulation Of Clu Expression In Cancer Cellsmentioning
confidence: 99%
“…Transforming growth factor beta-1 (TGF-b1) was shown to enhance sCLU protein and mRNA expression in thyroid epithelial cells, and it was proposed that upregulation of CLU expression may be a marker of TGF-b1-mediated thyrocyte dedifferentiation. 34 In rodent cells, CLU gene expression was proposed to occur via a consensus AP-1-binding site located in the promoter region of this gene. 15 Furthermore, TGF-b1-induced CLU expression in CCL64 mink lung cancer cells was repressed by overexpression of the c-Fos proto-oncogene, and it was speculated that TGF-b1 could exert effects on c-Fos protein synthesis and/or stability, resulting in the repression of c-Fos, and thus increased CLU gene expression.…”
Section: Regulation Of Clu Expression In Cancer Cellsmentioning
confidence: 99%